Prevalence of erectile dysfunction and associated factors among newly diagnosed ART naïve men living with HIV: a cross sectional study in Mwanza, Northwestern Tanzania - Iddi, Shabani; Matovelo, Dismas; Marwa, Karol J.; Kidenya, Benson R.; Dika, Haruna; Kalluvya, Samuel E. (Frontiers in Urology, 2025)
BackgroundErectile dysfunction (ED) is a frequent finding in men living with human immunodeficiency virus (HIV) (MLWH) and this remains a major concern because of its negative impact on the quality of life of those affected. There is limited data about the magnitude of ED and associated factors among MLWH in Tanzania. Thus this study was aimed to determine the prevalence of ED and associated factors among newly diagnosed antiretroviral therapy (ART)-naive MLWH in Mwanza, Northwestern Tanzania.MethodsA cross-sectional study was conducted among 373 newly diagnosed ART-naïve MLWH attending voluntary counseling and testing centers of four selected hospitals in Mwanza region who were consecutively enrolled and subjected to thorough clinical and general physical examination, including anthropometric measurements. A pre-structured questionnaire was used to collect socio-demographic characteristics and clinical data. ED was assessed using the International Index of Erectile Function–5. Serum total testosterone, follicle-stimulating hormone, luteinizing hormone and estradiol were estimated. Data were entered in Microsoft Excel, cleaned and analyzed using STATA version 15.ResultsOf the 373 analyzed participants with a median age of 40 [IQR: 33–46] years, ED was found in 56.3% (95% CI 51.2%–61.3%), whereas the majority presented with mild (45.2%) to mild-moderate (40.0%) ED. The median testosterone was significantly lower in men with ED as compared with men without (294.5 [135–469] versus 482 [191–602] ng/ml; p<0.001). In a multivariate logistic regression analysis, ED showed significant association with World Health Organization (WHO) clinical stage 4 for HIV infection (AOR 3.2; 95% CI 1.1–9.2; p=0.032), low testosterone level (AOR 1.9; 95% CI 1.2–3.0; p=0.010), and being non-self-employed (AOR 3.7; 95% CI 2.0–7.0; p<0.001).ConclusionED was found in more than half of ART naïve MLWH. The majority had a mild to mild-moderate ED. There was a significant association between ED and WHO clinical stage 4 for HIV infection, low testosterone level, and being non-self-employed. This finding emphasizes the need to routinely screen for early detection and management of ED in care and treatment center (CTC) clinics.